INTEGRATING ISLAMIC LEGAL LITERACY AND FAMILY SUPPORT IN SHAPING MARRIAGE READINESS: A STRUCTURAL EQUATION MODELING APPROACH: Integrasi Literasi Hukum Islam dan Dukungan Keluarga dalam Membentuk Kesiapan Menikah: Pendekatan Model Persamaan Struktural - Sabilul Muhtadin; Abd.Muthalib; Marwan Mas'ud; Muhammad Yassir; Riyan Maulana Sidiq (Jurnal Ilmu Keluarga dan Konsumen, 2026)
Marriage readiness among Muslim young adults is increasingly shaped by the interplay between cognitive and social factors in contemporary society. This study examines the direct and indirect relationships between Fiqh al-Munakahat literacy, family support, and marriage readiness among students in Islamic higher education institutions in Indonesia. A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to data collected from 155 students through purposive sampling. The findings reveal that Fiqh al-Munakahat literacy significantly influences both family support (β = 0.456, p < 0.001) and marriage readiness (β = 0.399, p < 0.001), while family support also significantly affects marriage readiness (β = 0.296, p < 0.001). The results indicate that cognitive factors play a more dominant role than social factors, suggesting that students increasingly rely on religio-legal understanding and self-confidence when preparing for married life. These findings contribute to the development of an integrated cognitive-social framework for strengthening marriage preparation programs in Islamic educational contexts.